Clinical characteristics and genetic analysis of cystic fibrosis transmembrane conductance reseptor‐related disease. Issue 5 (28th May 2020) - Kilinc, Ayse Ayzit; Alishbayli, Gulizar; Taner, Hasan Emir; Cokugras, Fugen Cullu; Cokugras, Haluk
Abstract: Background: Cystic fibrosis (CF) transmembrane conductance receptor (CFTR)‐related disease is diagnosed in patients affected by CFTR dysfunction who do not fully meet the CF diagnostic criteria. Only 2% of all CF patients have CFTR‐related disease. We define the demographic characteristics of such patients, described the performance of mutational analyses, and describe the clinical findings. Methods: Twenty‐four patients were followed‐up for CFTR‐related disease. Patients with CF symptoms but who did not completely fulfil the CF diagnostic criteria were enrolled. Age, body mass index at the times of diagnosis and admission, symptoms, pulmonary function and fecal elastase test results, gene analyses, and clinical findings during follow‐up were evaluated. Results: Ten patients (42%) were female and 14 (58%) male. Their mean age was 15.3 years (minimum–maximum 6–20 years). The mean age at diagnosis was 8.5 years (minimum–maximum 3–14 years) and the most common presenting complaint was a cough ( n = 19). During follow up, chronic sinusitis developed in 15 patients, bronchiectasis in 13, nasal polyposis in six, failure to thrive in three, recurrent pancreatitis in two, asthma in one, and congenital bilateral absence of the vas deferens in one. Fecal elastase levels were low in only one of the three patients who failed to thrive. In terms of CFTR gene mutations, two were found in 10 patients, one in eight patients, and none in six. Conclusions: Cystic fibrosis transmembrane conductance receptor‐related disease presents with various clinical findings. Serious symptoms may develop later in life. Late diagnosis significantly compromises the quality and duration of life in such patients.